ANALISIS FAKTOR KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN BIOLOGI DI KELAS XI MIA SMA NEGERI 3 LAHUSA TAHUN AJARAN 2022/2023 - Laia, Widasari (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2023)
This study aims to be able to identify the factors that cause learning difficulties experienced by students in learning biology. This research was conducted descriptive method through interviews. The number of informants in the interviews increased to 16 people by asking questions about the factors and causes of student learning difficulties. The research tool used is an interview form. The data collection technique in this study used an interview questionnaire which was made based on the causes of student learning difficulties. Based on this research, it can be seen that the factors that make it difficult for students to study in class XI Mia SMA Negeri 3 Lahusa are lack of attention and concentration, which causes inappropriate teaching, in this case the teaching process that students like in class is not noticed by the teacher, does not adjust method with the situation or too monotonous and focused on the topic. Then the less conducive classroom environment makes students bored with the delivery of confusing material accompanied by humor. Thus, students get a negative impact by getting low scores on biology assignments. Through this research, it is hoped that subject teachers will be able to choose and adapt methods to situations and conditions. From the results of this study it can be concluded that the cause of student learning is the lack of concentration and attention of students when studying.